The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1007/s11295-018-1297-2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation and signatures of natural selection in populations of European beech (Fagus sylvatica L.) along precipitation gradients

Abstract: European beech (Fagus sylvatica L.) is one of the most important forest tree species in Europe, and its genetic adaptation potential to climate change is of great interest. Saplings and adults from 12 European beech populations were sampled along two steep precipitation gradients in Switzerland. All individuals were genotyped at 13 microsatellite markers and 70 SNPs in 24 stress response and phenology related candidate genes. Both SSR and SNP markers had high genetic diversity in the studied populations and lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 129 publications
3
32
0
Order By: Relevance
“…Beech populations across central Europe have been shown to be genetically closely related in terms of neutral markers, such as microsatellite loci, but to differ in genes related to adaptive traits (e.g., Buiteveld et al, 2007). Nevertheless, genotypic diversity has often been found to be larger within than among populations, also including also adaptive traits (e.g., Cuervo-Alarcon et al, 2018). In contrast to the lack of studies on acclimation to changes in nutrient supply, the ability of beech populations from sites with different climatic conditions to acclimate, in the short term, to increased drought frequency has recently received much attention (Meier and Leuschner, 2008;Cuervo-Alarcon et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beech populations across central Europe have been shown to be genetically closely related in terms of neutral markers, such as microsatellite loci, but to differ in genes related to adaptive traits (e.g., Buiteveld et al, 2007). Nevertheless, genotypic diversity has often been found to be larger within than among populations, also including also adaptive traits (e.g., Cuervo-Alarcon et al, 2018). In contrast to the lack of studies on acclimation to changes in nutrient supply, the ability of beech populations from sites with different climatic conditions to acclimate, in the short term, to increased drought frequency has recently received much attention (Meier and Leuschner, 2008;Cuervo-Alarcon et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, genotypic diversity has often been found to be larger within than among populations, also including also adaptive traits (e.g., Cuervo-Alarcon et al, 2018). In contrast to the lack of studies on acclimation to changes in nutrient supply, the ability of beech populations from sites with different climatic conditions to acclimate, in the short term, to increased drought frequency has recently received much attention (Meier and Leuschner, 2008;Cuervo-Alarcon et al, 2018). Specifically, Meier and Leuschner (2008) found that while root traits, such as relative fine root growth and turnover, of beech populations from sites differing in precipitation responded generally strongly to drought treatment, the effect of provenance was small.…”
Section: Introductionmentioning
confidence: 99%
“…samβada is written in C++ with a particular emphasis on high-performance computing (HPC). Since its publication, samβada, as applied alone or in combination with other methods, proved useful to target putative genomic regions underlying local adaptation in a wide variety of species, including domestic animals such as swine and cattle (Cesconeto et al, 2017;Vajana et al, 2018), wild animals such as the freshwater sculpin and European pond turtle (Lucek, Keller, Nolte, & Seehausen, 2018;Pereira, Teixeira, & Velo-Antón, 2018), and many different plant species including the European beech and the cow-tail fir (Cuervo-Alarcon et al, 2018;Shih, Chang, Chung, Chiang, & Hwang, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Despite these caveats, F ST outlier methods have been used in a large number of studies and has brought emblematic allele discoveries at genes involved in adaptation to different environment conditions (Feulner et al, 2015;Wang et al, 2015;Elgvin et al, 2017;Fustier et al, 2017). However, BayeScan has been considered more conservative in identifying outlier SNPs than other methods (Narum and Hess, 2011b;Cuervo-Alarcon et al, 2018;Gros-Balthazard et al, 2019), and its power to detect outliers depends largely on sample size and number of sampled populations (Lotterhos and Whitlock, 2015;Ahrens et al, 2018). Considering that, in this study, only two populations are involved in each comparison, so, we solely used F ST scan to detect outlier SNPs.…”
Section: Discussionmentioning
confidence: 99%